Implementation Of Problem-Based Learning Strategies In Vocational Secondary Schools In The Field Of Technology And Engineering Skills - Setyowati, Arum; Rusmono, Rusmono (Peneliti.net, 2023)
The research aims to determine the influence of learning strategies and Mathematicsanxiety on learning outcomes in the PRE (PRE). The research was carried out at SMKNegeri 7 Bekasi City, West Java. Using experimental methods with a 2x2 factorial groupdesign. The research sample consisted of 36 students selected randomly. The researchresults show that the PRE learning outcomes of students who use PBL learning strategiesare higher than those who use direct learning strategies after controlling for Mathematicsanxiety. There is an interaction effect between learning strategies and anxiety on students'PRE learning outcomes after controlling for Mathematics anxiety. The PRE learningoutcomes of students who use PBL learning strategies for students who have high levels ofMathematics anxiety are higher than students who use direct learning strategies. The PRElearning outcomes of students who use PBL learning strategies for students who have lowanxiety are lower than students who are taught using direct learning strategies. It can beconcluded that there is an interaction effect between the use of learning strategies andMathematics anxiety on PRE learning outcomes.